PENINGKATAN KAPASITAS RUMAH TANGGA PERIKANAN DI NEGERI TIAL KABUPATEN MALUKU TENGAH - Nanlohy, Hellen; Latubual, Ida; Idonggoleng, Elisabeth (Pattimura University, 2022)
Tial Country is one of the countries in Saluhutu District, Central Maluku Regency, Maluku Province which has great fisheries potential because of its geographical location in the Coastal Area. Most people have a livelihood as fishermen. The target of this counseling activity is to increase the capacity of fishery households consisting of fishermen, fishermen's wives and family members who work in the fisheries sector. The counseling method is carried out by the method of lectures and discussions. The results of this counseling on increasing the capacity of fishermen show that the community understands the importance of maintaining and protecting the sustainability of fishery resources. The community must also participate in maintaining and maintaining the sustainability of fishery resources. The community feels an increase in knowledge and skills. This counseling is a suggestion that is very relevant to the condition of coastal areas and the available fishery resources